MICROSOFT FABRIC DATA WAREHOUSE: A DEEP DIVE INTO THE POLARIS ANALYTIC ENGINE - Pradeep Kumar Vattumilli (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Microsoft Fabric Data Warehouse, powered by the Polaris distributed SQL query engine, represents a transformative advancement in cloud-native data processing solutions. This article explores the architecture, capabilities and implementation aspects of the platform, focusing on its stateless design, performance optimization features, and enterprise integration capabilities. The article examines the platform's core components, including its distributed processing framework, storage architecture, and compute layer design, while highlighting the benefits of storage and compute separation. Through detailed examination of implementation best practices and integration strategies, this article demonstrates how Microsoft Fabric Data Warehouse addresses modern enterprise data management challenges while providing scalable, secure, and efficient data processing capabilities.